The Potential of Red Dragon Fruit (Hylocereus polyrizhus) as a Hair Dye - Prayoga Dafa Sundawan; Satrio Adi Putra; Mochamad Raka Werdaya; Nia Yuniarsih (Archives of The Medicine and Case Reports, 2022)
Hair coloring is the act of changing the hair color, which has been known since the times of Egypt, Ancient Greece, Ancient China, and India. At that time, the colors used that came from plants were called vegetable dyes or traditional dyes, where the coloring was done to change the original hair color or to cover gray hair and follow the existing trends. Natural dyes are not only used as medicine but can also be used as cosmetic dyes. One of the natural ingredients that can be used to make hair dye preparations is the skin of red dragon fruit (Hylocereus Polyrhizus). In general, dragon fruit skin is rarely used properly, even thrown away when finished) It's just that many people don't know how to use it, thus increasing the amount of waste from dragon fruit skin.